Occurrence of toxigenic microalgal species and phycotoxins accumulation in mesozooplankton in Northern Patagonian gulfs, Argentina - D'Agostino, Valeria C. (2019)
In the Northern Patagonian gulfs of Argentina (Golfo Nuevo and Golfo San José), blooms of toxigenic microalgae and the detection of their associated phycotoxins are recurrent phenomena. The present study evaluated the transfer of phycotoxins from toxigenic microalgae to mesozooplankton in Golfo Nuevo and Golfo San José throughout an annual cycle (December 2014–2015 and January 2015–2016, respectively). In addition, solid‐phase adsorption toxin tracking (SPATT) samplers were deployed for the first time in these gulfs, to estimate the occurrence of phycotoxins in the seawater between the phytoplankton samplings. Domoic acid was present throughout the annual cycle in SPATT samplers, whereas no paralytic shellfish poisoning toxins were detected. Ten toxigenic species were identified: Alexandrium catenella, Dinophysis acuminata, Dinophysis acuta, Dinophysis tripos, Dinophysis caudata, Prorocentrum lima, Pseudo‐nitzschia australis, Pseudo‐nitzschia calliantha, Pseudo‐nitzschia fraudulenta, and Pseudo‐nitzschia pungens. Lipophilic and hydrophilic toxins were detected in phytoplankton and mesozooplankton from both gulfs. Pseudo‐nitzschia spp. were the toxigenic species most frequent in these gulfs. Consequently, domoic acid was the phycotoxin most abundantly detected and transferred to upper trophic levels. Spirolides were detected in phytoplankton and mesozooplankton for the first time in the study area. Likewise, dinophysistoxins were found in mesozooplankton from both gulfs, and this is the first report of the presence of these phycotoxins in zooplankton from the Argentine Sea. The dominance of calanoid copepods indicates that they were the primary vector of phycotoxins in the pelagic trophic web.